Rút gọn biểu thức:
A=1 + 1/2 + 1/22 + 1/32 + ..... + 1/22012
11. Rút gọn biểu thức:
A = (3 + 1) (32 + 1) (34 + 1) ... (364 + 1)
\(\left(3-1\right)A=\left(3-1\right)\left(3+1\right)\left(3^2+1\right)\left(3^4+1\right)...\left(3^{64}+1\right)\\ 2A=\left(3^2-1\right)\left(3^2+1\right)\left(3^4+1\right)...\left(3^{64}+1\right)\\ 2A=\left(3^4-1\right)\left(3^4+1\right)...\left(3^{64}+1\right)\\ 2A=\left(3^8-1\right)\left(3^8+1\right)...\left(3^{64}-1\right)\\ ...\\ 2A=\left(3^{64}-1\right)\left(3^{64}+1\right)\\ 2A=3^{128}-1\)
Vậy \(A=\dfrac{3^{128}-1}{2}.\)
Rút gọn biểu thức:
A = \(\dfrac{1}{2+\sqrt{3}}\) + \(\dfrac{1}{2-\sqrt{3}}\)
Rút gọn biểu thức:A=1+1/2+1/22+1/23+...+1/22012
Ta có :
\(A=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{2012}}\)
\(2A=1+2+\frac{1}{2}+...+\frac{1}{2^{2011}}\)
\(2A-A=\left(1+2+\frac{1}{2}+...+\frac{1}{2^{2011}}\right)-\left(1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{2012}}\right)\)
\(A=2-\frac{1}{2^{2012}}\)
\(A=\frac{2^{2013}-1}{2^{2012}}\)
Vậy \(A=\frac{2^{2013}-1}{2^{2012}}\)
Rút gọn biểu thức:A=1+1/2 +1/22+1/23+...+1/22012
\(A=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{2012}}\)
=>2A=\(2+1+\frac{1}{2}+...+\frac{1}{2^{2011}}\)
=>2A-A=\(\left(2+1+\frac{1}{2}+...+\frac{1}{2^{2011}}\right)-\left(1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{2012}}\right)=2-\frac{1}{2^{2012}}\)
=>A=\(\frac{2^{2013}-1}{2^{2012}}\)
Rút gọn biểu thức:
A=\(\dfrac{1}{\sqrt{3}+1}+\dfrac{1}{\sqrt{3}-1}\)
`A=1/[\sqrt{3}+1]+1/[\sqrt{3}-1]`
`A=[\sqrt{3}-1+\sqrt{3}+1]/[3-1]`
`A=[2\sqrt{3}]/2=\sqrt{3}`
\(A=\dfrac{1}{\sqrt{3+1}}+\dfrac{1}{\sqrt{3-1}}\)
\(A=\dfrac{\sqrt{3-1+\sqrt{3+1}}}{\left(\sqrt{3+1}\right)\left(\sqrt{3-1}\right)}\)
\(A=\dfrac{2\sqrt{3}}{3-1}\)
\(A=\dfrac{2\sqrt{3}}{2}\)
\(A\sqrt{3}\)
\(A=\dfrac{1}{\sqrt{3}+1}+\dfrac{1}{\sqrt{3}-1}\)
\(A=\dfrac{\sqrt{3}-1+\sqrt{3}+1}{3-1}\)
\(A=\dfrac{2\sqrt{3}}{2}\)
\(A=\sqrt{3}\)
Rút gọn biểu thức:
A = \([(32)^{\dfrac{2}{3}}]^{\dfrac{-2}{5}}\)
B= \(\dfrac{x^{-2}+y^{-2}}{x^{-1}+y^{-1}}\)
C = \((a^{\dfrac{1}{3}}-b^{\dfrac{2}{3}})(a^{\dfrac{2}{3}}+a^{\dfrac{1}{3}}×b^{\dfrac{4}{3}}+b^{\dfrac{4}{9}})\)
D = \((x+y^\dfrac{3}{2}÷\sqrt{x})^\dfrac{2}{3}÷[\dfrac{\sqrt{x}-\sqrt{y}}{\sqrt{x}}+\dfrac{\sqrt{y}}{\sqrt{x}-\sqrt{y}}]^\dfrac{2}{3}\)
E = \([\dfrac{1}{x^{\dfrac{1}{2}}-4x^{\dfrac{-1}{2}}}-\dfrac{2\sqrt[3]{x}}{x\sqrt[3]{x}-4\sqrt[3]{x}}]^{-2}-\sqrt{x^2+8x+16}\)
Cho 2 biểu thức:
A = \(\dfrac{x+2}{x\sqrt{x}-1}+\dfrac{\sqrt{x}+1}{x+\sqrt{x}+1}\)
B = \(\dfrac{1}{\sqrt{x}-1}\)
Rút gọn biểu thức A - B
\(A=\dfrac{x+2+x-1-x-\sqrt{x}-1}{\left(\sqrt{x}-1\right)\left(x+\sqrt{x}+1\right)}\)
\(=\dfrac{\sqrt{x}}{x+\sqrt{x}+1}\)
Rút gọn biểu thức:
a) (2x + 1)2 + (2x - 1)2 - 2(x - 3)2
b) (x - 1)2 - (3x + 2)2
c) (6x + 1)2 + (6x - 1)2 - 2(1 + 6x) (6x - 1)
Rút gọn biểu thức:
a) (2x + 1)2 + (2x - 1)2 - 2(x - 3)2
b) (x - 1)2 - (3x + 2)2
c) (6x + 1)2 + (6x - 1)2 - 2(1 + 6x) (6x - 1)
a: \(\left(2x+1\right)^2+\left(2x-1\right)^2-2\left(x-3\right)^2\)
\(=4x^2+4x+1+4x^2-4x+1-2\left(x^2-6x+9\right)\)
\(=8x^2+2-2x^2+12x-18\)
\(=6x^2+12x-16\)
b: \(\left(x-1\right)^2-\left(3x+2\right)^2\)
\(=x^2-2x+1-9x^2-12x-4\)
\(=-8x^2-14x-3\)
c: \(\left(6x+1\right)^2+\left(6x-1\right)^2-2\left(6x+1\right)\left(6x-1\right)\)
\(=\left(6x+1\right)^2-2\left(6x+1\right)\left(6x-1\right)+\left(6x-1\right)^2\)
\(=\left(6x+1-6x+1\right)^2=2^2=4\)